2011
DOI: 10.3109/0886022x.2011.568134
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene-Vinyl Alcohol Copolymer Dialyzer Membrane Reduces Protein Oxidation in Hemodialysis Patients

Abstract: Background: Oxidative stress has been implicated in the cardiovascular complications that affect hemodialysis (HD) patients. Ethylene-vinyl alcohol copolymer (EVAL) dialyzer membrane induces less production of reactive oxygen species as compared to conventional dialyzers. We evaluated the impact of EVAL membrane on plasma protein oxidation in HD patients. Methods: HD patients treated with cellulose triacetate (CTA) dialyzers were selected. In the first study performed in a 2-month crossover design alternating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Fabrication of Zeolite/EVOH Nanofiber Mesh. We have previously reported fabrication of zeolite/EVOH nanofiber mesh using an isopropanol or HFIP solvent system [19]. We found that isopropanol solution could only be electrospun for a couple of hours as the EVOH would start to come out of solution.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Fabrication of Zeolite/EVOH Nanofiber Mesh. We have previously reported fabrication of zeolite/EVOH nanofiber mesh using an isopropanol or HFIP solvent system [19]. We found that isopropanol solution could only be electrospun for a couple of hours as the EVOH would start to come out of solution.…”
Section: Resultsmentioning
confidence: 98%
“…Lou et al, on the other hand, used EVOH membranes to investigate the effects of senescence-associated phenotypic changes on the cellular aging process [15]. EVOH membrane has been also applied to HD patients as a dialyzer membrane and shown minimal platelet activation and little generation of reactive oxygen species by activated neutrophils [19]. Zeolites are aluminosilicates which have microporous structures capable of adsorbing toxins such as creatinine from blood [20][21][22][23][24][25].…”
Section: Journal Of Nanomaterialsmentioning
confidence: 99%
“…This may because PFOA and PFOS are both hydrophobic materials and are more easily cleared using hydrophobic membranes. Previous studies showed membrane properties have a considerable influence on inflammation, platelet activation, and phagocytes [ 22 ]. To the best of our knowledge, this is the first study that proves the hydrophobic or hydrophilic properties of membranes can infuence the concentrations of environemental pollutants.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to cellulose membranes, organic synthetic membranes possess more physical-chemical advantages in terms of pore size, hydraulic permeability and filtration capacity. [28,53,[60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Polysulfone (PS) [61][62][63][64][65] and polyethersulfone (PES) [66][67][68][69][70] membranes are two of the most classical synthetic membranes, which have been widely used in clinical hemodialysis due to their excellent filtering properties and biocompatibility, thermal stability, mechanical strength, and chemical inertness. However, the intrinsic hydrophobicity of PS membranes often causes the adsorption of serum proteins, leading to serious complications.…”
Section: Organic Synthetic Membranesmentioning
confidence: 99%
“…[82][83][84] The heparin-immobilized PLA membrane showed excellent blood compatibility and low toxicity. More recently, Yang and co-workers reported a nontoxic, Small 2020, 16,1904076 [56,57] Modified cellulose membrane Acetate grouped CM Better blood compatibility than CM Limited in clearance of middle [58] Diethylaminoethyl grouped CM molecules and macromolecules [59] Benzyl grouped CM [55] Organic synthetic membrane Polysulfone (PS) Excellent physical and chemical properties; Good mechanical strength; Efficient clearance of middle molecules and macromolecules Lower blood compatibility than biodegradable membrane and protein membrane [61][62][63][64][65] Polyethersulfone (PES) [66][67][68][69][70] Polyamide (PA) [71] Polyacrylonitrile (PAN) [72,73] Poly(methyl methacrylate) (PMMA) [65,74] Polycarbonate (PC) [49] Ethylene-vinyl alcohol copolymer (EVAL) [75] Polyvinylidene Fluoride (PVDF) [28] Polyurethane (PU) [28] Inorganic ultrathin protein membrane with high molecule cleaning efficiency. The protein membrane was fabricated by amyloid-like lysozyme oligomer self-assembly.…”
Section: Biodegradable Membranes and Bioactive Membranesmentioning
confidence: 99%